Simultaneous removal of organic pollutants and heavy metals in wastewater by photoelectrocatalysis: A review. (June 2021) - Ye, Shangshi; Chen, Yingxu; Yao, Xiaoling; Zhang, Jingdong
Abstract: As a powerful technique by combining photocatalysis with electrochemistry, photoelectrocatalysis has been extensively explored to simultaneously remove mixed pollutants of organic and heavy metal in wastewater in the past decade. In the photoelectrocatalytic system, the bias potential can remarkably promote the oxidation of organic pollutants on the photoanode by suppressing the recombination of photogenerated electron-hole pairs and extending the lifetime of photogenerated holes. Meanwhile, some photogenerated electrons are driven by the bias potential to the cathode to reduce heavy metals. In this review, we summarize the research advances in photoelectrocatalytic treatment of organic-heavy metal mixed pollution systems under UV light, visible light and sunlight. We demonstrate the main operation variables affecting the photoelectrocatalytic removal processes of organic pollutants and heavy metals. The problems for utilization of solar energy in photoelectrocatalysis are discussed. Finally, this review proposes the perspectives for future development of photoelectrocatalysis to industrial applications. Graphical abstract: Image 1 Highlights: PEC treatment of wastewater containing organic pollutant and heavy metal is reviewed. The advantages of PEC techniques for treating mixed pollution systems are explained. The problems and future development direction for PEC technique are discussed.